KOMPLEKSITAS TUGAS DAN SISTEM, SERTA STRUKTUR ORGANISASI MEMODERASI HUBUNGAN PARTISIPASI DENGAN KEPUASAN PEMAKAI SISTEM INFORMASI - Andriyani, Lilik (Universitas Muhammadiyah Magelang, 2007)
This research aim to know how far influence of duty complexity, complexity of system and organization chart as moderating variable in relation of among participation of user and user satisfaction in system development, as well as to know how far influence participate the user to user satisfaction in course of system development information. Test the hypothesis onducted at 66 responder which is gone the round of at 35 manufacturing business and services of exist in Central Java region. Technique of intake sample in this research use the convinience sampling. Research method in hypothesis test use the linear regression to test the influence participate the wearer to wearer satisfaction in system development information, while test of variable moderating condusted by using method MRA (Moderated Regression Analysis). Result of research indicated that user participation has a significant rewlationship with user satisfaction in the development information system. Duty complexity non representing variable moderating of among relation participate the user with the user satisfaction, but as independent variable. System complexity representing as variable moderating of among relation participate the user with the user satisfaction, while organization chart representing as variable moderating of among relation participate the user with the user participate.